If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.6x + 11 + 1.3 + 2x = 0 Reorder the terms: 11 + 1.3 + -6.6x + 2x = 0 Combine like terms: 11 + 1.3 = 12.3 12.3 + -6.6x + 2x = 0 Combine like terms: -6.6x + 2x = -4.6x 12.3 + -4.6x = 0 Solving 12.3 + -4.6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12.3' to each side of the equation. 12.3 + -12.3 + -4.6x = 0 + -12.3 Combine like terms: 12.3 + -12.3 = 0.0 0.0 + -4.6x = 0 + -12.3 -4.6x = 0 + -12.3 Combine like terms: 0 + -12.3 = -12.3 -4.6x = -12.3 Divide each side by '-4.6'. x = 2.673913043 Simplifying x = 2.673913043
| -14+s=6 | | 2(2k*1)=4(k*2) | | 3x+18=5x+20 | | -5(7p-1)-(1+2p)=3+8p+1 | | -11+r=5 | | 8x-2x+5x= | | 4a+2a-3a=9 | | 13b-39=2 | | 67=-8+5x | | 8.2+1.6x=x+20.7 | | -16=8a-6a | | 4y-18=6y+4 | | -1=-4x+3 | | p=x+(2x+-4)+(2x+-4) | | 4(4n-1)=-2(n+2) | | 210+4x=64 | | p=(2x-4)(2x-4) | | n/3--8=-2 | | 8(5x-3)3.2= | | 5x-4x=2 | | -4k+3=11 | | -(4+12x)=32 | | 100=2(3.14)r | | 75=19 | | 6+8q=11x+7q | | x^2-40x+3200=0 | | -4+3=11 | | 4-3x=x-6 | | 6(8+x)-6x=8(x+5) | | 2x^2+12=-5x | | 0.30(x+10)+0.30x=12 | | 2(x+7)=5x-35 |